THE ROLE OF ORGANIZATIONAL CULTURE AND ENTREPRENEURSHIP ORIENTATION ON EMPLOYEE PERFORMANCE IN VILLAGE CREDIT UNION IN BADUNG - BALI - Artini, Ni Rai; Pynatih, Ngurah Made Novianha; Ayuk, Ni Made Taman; Marta, I Nyoman Gede (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2022)
The performance of Village Credit Union employees in Bali tends to decline. In addition to financial factors, it is suspected that this is also influenced by non-financial factors, namely entrepreneurial orientation and organizational culture. This study examines the influence of organizational culture and entrepreneurial orientation on employee performance at the village credit union in Badung Regency. These four main objectives are achieved by using a quantitative approach. The quantitative approach uses an alternative PLS 3 SEM analysis technique, using 94 respondents from Village Credit Union employees in Badung Regency. The results of the study show that organizational culture influences entrepreneurial orientation. However, organizational culture does not affect employee performance. Entrepreneurial orientation is also proven to influence employee performance. In addition, entrepreneurial orientation can mediate organizational culture's influence on employee performance.